Supply chain integration and operational performance: The contingency effects of production systems. Issue 4 (October 2018) - Shou, Yongyi; Li, Ying; Park, Youngwon; Kang, Mingu
Abstract: The boundary conditions of supply chain integration (SCI) have been widely studied in order to find out when SCI is applicable and effective. However, prior studies have mainly focused on external contextual factors, such as supply complexity, environmental uncertainty and country-level infrastructure. This study contributes to the SCI literature by examining the contingency effects of internal production systems on the relationship between supplier integration, customer integration and operational performance. Based on organizational information processing theory, we provide evidence to show that the impact of supplier and customer integration on operational performance varies across production systems, such as one-of-a-kind production, batch production and mass production systems. The empirical results also reveal how supplier and customer integration can be matched with different configurations of production systems in order to achieve the desired quality, flexibility, delivery or cost performance. Highlights: The performance effect of supply chain integration varies across production system. Customer integration improves the one-of-a-kind production performance. Supplier integration improves the batch production performance. Supplier integration only contributes to the cost performance of mass production.